ENGLISH AS AN INTERNATIONAL LANGUAGE (EIL) AND IMPLICATIONS FOR ENGLISH LANGUAGE TEACHING - Hepy Adityarini (Universitas Muhammadiyah Surakarta, 2007)
The nature of English as an International Language (EIL) has significant implicationsin the area of English Language Teaching (ELT). The current essay willreview the implications of EIL in three different areas: research on attitudes towardsvarieties of English, research on methods of improving non-native speakers’intelligibility, English teaching curriculum and materials for teaching pronunciation.Despite the debate of appropriateness of native speakers’ accent as modelsfor teaching pronunciation, the findings from most of the research on attitudestowards varieties of English suggest the students’ preferences towards native speakers’accent. In the mean time, the research on methods of improving non-nativespeakers’ intelligibility indicate the necessity of giving more emphasis on teachingsuprasegmental features such as intonation and stress to non-native speakers. Atthe curriculum level, although the experts have proposed some ideas of how EILshould be, the implementation of such curriculum might be difficult to realize insome countries. With regards to pronunciation teaching materials, many Englishpractitioners recommend the use of authentic materials that incorporate students’local culture in the classroom.